Tinjauan Yuridis terhadap Penyelesaian Wanprestasi Perjanjian Asuransi dalam Putusan No. 537/Pdt.g/2013/PN.MDN - Siallagan, Arnol Faisal; Siregar, Taufik (Universitas Medan Area, 2017)
Juridical Review Of Completion Of Insurance Agreement Wanprestation in No. 537/Pdt.g/2013/PN.MDNAbstractInsurance is a legal term (legal term) used in legislation and insurance companies. The term insurance comes from the word